2012
DOI: 10.1097/scs.0b013e31824ddc43
|View full text |Cite
|
Sign up to set email alerts
|

Closure of Nasal Floor by Mucosal Flaps on the Upper Lip Margin in Wide Unilateral Complete Cleft Lip

Abstract: The technique serves to close the nasal floor with ease and safety, which aids the repair of wide unilateral complete cleft lip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…As mentioned earlier, no complications were detected among the participants of our study; however, infection, bleeding, ischemia, flap necrosis, complications associated with the harvesting procedure, graft deviation, obvious scar, excessive decrease in the nostril size, impaired ventilation, shortening of the upper lip, and sensory dysfunction are among potential complications, which require strict considerations, especially in the follow-up examinations [ 10 , 20 , 23 , 25 ].…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…As mentioned earlier, no complications were detected among the participants of our study; however, infection, bleeding, ischemia, flap necrosis, complications associated with the harvesting procedure, graft deviation, obvious scar, excessive decrease in the nostril size, impaired ventilation, shortening of the upper lip, and sensory dysfunction are among potential complications, which require strict considerations, especially in the follow-up examinations [ 10 , 20 , 23 , 25 ].…”
Section: Discussionmentioning
confidence: 67%
“…Patient dissatisfaction about obvious scars on upper lips ( N =3). [ 22 , 23 ] 20 A semi-open rhinoplasty technique Tajima incision on the cleft side and a Rim incision on the contralateral side Complete UCL 45 AB (along the scar line) Complete UCL Straight-Line Advanced Release Technique (StART) 72 AB (along the scar line) 5 years Symmetry between the sill areas, minimal scar in all cases NCR [ 9 ] Unilateral or bilateral complete cleft Performing 2 medial and lateral upper lip mucosal flaps. The medial flap was sutured to the lateral nasal mucosa, forming the upper layer of the nasal floor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If it is not wide, the undersurface of the repaired nostril floor usually is healed by the granulation tissue and is covered by mucosa on the oral side even if there are raw surfaces or surgical defects. The so-called wide cleft lip refers to when the ratio of the gap width to the upper lip length on the normal side is 8:10 or higher [ 4 ]. The patients in this study, except for number 3, showed a wide cleft lip.…”
Section: Case Presentationmentioning
confidence: 99%
“…He turned this flap upward by 180° and closed the pyriform aperture defect [ 7 ]. Chang et al also used this type of lip mucosal flap in a wide unilateral complete cleft lip [ 4 ]. In the present technique, the base of the lateral mucosal flap is wider and the circulation comes from the alveolus and the nasal wall.…”
Section: Case Presentationmentioning
confidence: 99%